'A Missed Therapeutic Opportunity? SGLT-2 Inhibitor Use in General Medicine Patients With Heart Failure: A Retrospective Audit of Admissions to a Tertiary Health Service'. Issue 16 (October 2022) - Perera, Padeepa; O'Donnabhain, Ronan; Fazio, Timothy; Johnson, Douglas; Lange, Peter
Objective: Sodium-glucose co-transporter-2 inhibitors (SGLT2-I's) are novel oral hypoglycaemic agents, with proven decreased MACE and re-hospitalisation risk in type 2 diabetic patients with concomitant heart failure. This study aimed to assess the current practice in the use of SGLT2-I's in general medical units at a large metropolitan health service. Methods/Results: A retrospective audit was conducted of patients admitted to general medicine over a 12 month period (between April 2018 and 2019). Inclusion criteria included decompensated heart failure of any aetiology and ejection fraction, and type 2 diabetes mellitus with an HbA1c ⩾ 7 within 6 months of the admission period. A total of 150 admissions fulfilled criteria. Baseline demographics and comorbidities identified an older, more comorbid population than reference trials. These included age (75% over 75 years), smoking history (46%), hypertension (83%), chronic kidney disease grade IV or V (26%), previous myocardial infarction (57%), stroke (18%), atrial fibrillation (55%) and known left ventricular ejection fraction < 50% (38%). Co-prescribed medications included ACE-I/ARB (53%), beta-blocker (67%), loop diuretic (87%), thiazide (7%), MRA (31%), insulin (57%), metformin (47%), sulphonylurea (31%), DPP-4 Inhibitor (21%), GLP-1 analogue (6%) and 15% of patients had an HbA1c > 10. There was a significant difference between patients in our study eligible for and prescribed metformin (66/111) compared to SGLT-2 inhibitors (4/25) ( P  = .013). A total of 26 patients had readmissions within 28 days, of which one had been discharged on an SGLT2-I. Conclusion: The results of this study identified significant under prescribing of SGLT2-I's in eligible type 2 diabetic patients with heart failure admitted under general medicine.